Beginning iOS Cloud and Database Development Build Data-Driven Cloud Apps for iOS - Ooley, Nathan. (Apress : Imprint: Apress, 2014)
Beginning iOS Cloud and Database Development gets you started with building apps that use Apple's iCloud. You'll learn the techniques which will enable you to devise and create iOS apps that can interact with iCloud servers. From the basics up, you'll progressively learn how to configure your app for iCloud, upload and download files, implement revisions, add conflict resolution policies, and work with custom documents. There's more! You'll learn how to integrate iCloud with Core Data based applications. Besides technical advice, you'll find suggestions and best practices to design the interaction of iCloud-driven applications. According to many industry sources, analysts, and shows, Apple will rely more and more on iCloud or web apps in the cloud to store and stream data-intensive media and other kinds of apps. As the majority of apps use some sort of data—and that only will grow as apps become more complex with rich and streaming media—this book shows developers how to create apps for iCloud, Apple's new cloud computing storage and data service.